HUBUNGAN BERAT BADAN LAHIR DAN CARA MENERAN DENGAN KEJADIAN DERAJAT LASERASI PADA PERSALINAN PRIMIGRAVIDA DI BPM JAWIRIYAH PUNGE KOTA BANDA ACEH - Kurniawati, Putri; Mauliati, Desria; Dewi, Rika; Amanda, Arianti; Ameliyah, Dela; Yanti, Yanti; Marissa, Hikmah (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
Based on data from BPM Jawiriyah, 114 mothers gave birth from January to June 2023, among them 40 primigravida mothers, the initial survey was conducted there were 7 primiparous mothers who experienced lacerations during childbirth, including 4 mothers who had a birth weight of more than 3500 grams and even 4000 grams, and there were 3 mothers who had a birth weight of 2500 grams. Based on these 7 mothers said that the cause of the laceration they experienced was due to the weight of the baby born and some were due to the wrong way of receiving in the process of labor. The purpose of the study was to determine the relationship between birth weight and the way of receiving with the incidence of laceration degree in primigravida labor at BPM Jawiriyah, S.ST in 2023. Research Methods, research is analytical using a Cross Sectional approach conducted on June 20-25, 2023 at BPM Jawiriyah, S. ST with a population of 40 laboring mothers. The research instrument was a questionnaire. Data analysis using univariate and bivariate analysis with the SPSS statistical program. The results of the statistical test with Chi Square obtained a p value = 0.086 (P>0.05) means that there is no relationship between laceration and baby weight in primigravida labor. While the results of statistical tests with Chi Square obtained a p value = 0.991 (P>0.05) means that there is no relationship between lacerations and how to deliver in primigravida labor. The conclusion is that there is no relationship between laceration and baby weight and how to deliver in primigravida labor